2014
DOI: 10.1111/srt.12136
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydration on the risk of friction blister formation on the heel of the foot

Abstract: In controlled experimental conditions increased skin surface hydration increases the rate of temperature change of the skin in response to load application and consequently increases the risk of blister creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
16
1
2
Order By: Relevance
“…In addition, the plasticizing effect of water on keratin causes the stratum corneum to become less stiff and more deformable therefore increasing the area of contact and therefore increasing friction [16][17][18]. Indeed, using a laboratory based model of blister formation, the authors have already demonstrated that greater skin hydration is associated with greater risk of foot blisters [11].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, the plasticizing effect of water on keratin causes the stratum corneum to become less stiff and more deformable therefore increasing the area of contact and therefore increasing friction [16][17][18]. Indeed, using a laboratory based model of blister formation, the authors have already demonstrated that greater skin hydration is associated with greater risk of foot blisters [11].…”
Section: Introductionmentioning
confidence: 95%
“…formation [11,33]. This approach enables the effects of interventions and any role of skin hydration in these effects to be studied more sensitively than in previous studies.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations